The quality of life of diabetes mellitus patients with diabetic retinopathy complications: A descriptive cross-sectional study - Diva Amanda Putri; Dona Amelia; Aulia Putri (Nurse Point: Journal of Nursing, 2025)
Background: Diabetic Retinopathy (DR) imposes a profound multidimensional burden on patients, extending beyond physiological visual loss to compromise daily functioning and psychosocial well-being. While the clinical progression of DR is well-documented, empirical evidence regarding its specific impact on quality of life (QoL) domains in developing regions remains limited Objective: This study aimed to describe the quality of life and identify specific functional deficits among patients with diabetes mellitus complicated by diabetic retinopathy in West Sumatra, Indonesia. Method: A quantitative descriptive cross-sectional study was conducted at the Eye Clinic of Ibnu Sina Yarsi Islamic Hospital, Bukittinggi. A total of 70 patients with confirmed diabetic retinopathy were recruited using purposive sampling. Data were collected using the validated Indonesian version of the National Eye Institute Visual Function Questionnaire-25 (NEI VFQ-25). Descriptive statistical analysis was performed to determine demographic characteristics and domain-specific QoL scores. Results: The study cohort was primarily female (61.4%) and elderly, with 64.3% of the participants being 60 years or older. Most participants had been living with diabetes for more than 10 years (68.6%). Overall, half of the participants (50.0%) reported a moderate quality of life, while 28.6% rated their quality of life as poor. Analysis of specific domains showed that "near activities" and "mental health" were the most significantly affected areas. In contrast, scores for "color vision" and "peripheral vision" were relatively well-preserved. Conclusion: diabetic retinopathy severely impacts patients' quality of life, particularly affecting their independence in near-vision tasks and their psychological well-being. These findings underscore the pressing need for comprehensive nursing interventions that encompass routine psychosocial assessments and education on adaptive self-management, in conjunction with clinical management of glycemic levels, to enhance the overall well-being of this vulnerable population